Alloying effect of Ni-Mo catalyst in hydrogenation of N-ethylcarbazole for hydrogen storage - Wang, Bin; Dong, Qian; Wang, Si-Yao; Li, Pei-Ya; Wang, Shi-Yuan; Lu, Shu-Han; Fang, Tao (Frontiers in Chemistry, 2022)
Liquid organic hydrogen storage with N-ethylcarbazole (NEC) as a carrier is a very promising method. The use of precious metal hydrogenation catalysts restricts the development in industrial grade. Efficient and low-cost hydrogen storage catalysts are essential for its application. In this work, a Ni-Mo alloy catalyst supported by commercial activated carbon was synthesized by impregnation method, and the Ni-Mo ratio and preparation conditions were optimized. The catalyst was characterized by XRD, XPS, H2-TPR, SEM, and TEM. The results showed that the doping of Mo could dramatically promote the catalytic hydrogenation of N-ethylcarbazole by the Ni-based catalyst. More than 5.75 wt% hydrogenation could be achieved in 4 h using the Ni-Mo catalyst, and the selectivity of the fully hydrogenated product 12H-NEC could be effectively improved. This result reduces the cost of hydrogenation catalysts by more than 90% and makes liquid organic hydrogen storage a scaled possibility.